2002
DOI: 10.1021/ja011852h
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Active Site of Cytochrome Oxidase:  Synthesis and Characterization of a Cross-Linked Histidine−Phenol

Abstract: A cross-linked histidine-phenol compound was synthesized as a chemical analogue of the active site of cytochrome c oxidase. The structure of the cross-linked compound (compound 1) was verified by IR, (1)H and (13)C NMR, mass spectrometry, and single-crystal X-ray analysis. Spectrophotometric titrations indicated that the pK(a) of the phenolic proton on compound 1 (8.34) was lower than the pK(a) of tyrosine (10.1) or of p-cresol (10.2). This decrease in pK(a) is consistent with the hypothesis that a cross-linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
169
3

Year Published

2002
2002
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(213 citation statements)
references
References 60 publications
40
169
3
Order By: Relevance
“…A peptide fragment in the former but not latter digest was identified that exhibited an unusual UV-visible spectrum for a polypeptide, with large bathochromic shifts of the major absorption bands. This alone suggested the presence of the Met-Tyr-Trp cross-link, as shifts for comparable aromatic-ring substitutions are predicted from theory (58) and observed in similar small molecule analogs, most notably for the cross-linked histidine-phenol mimic of cytochrome c oxidase (71), which exhibits a red-shift of ϳ20 nm of the phenol B (tyrosine) band (from 280 to ϳ300 nm).…”
Section: Fig 10supporting
confidence: 70%
“…A peptide fragment in the former but not latter digest was identified that exhibited an unusual UV-visible spectrum for a polypeptide, with large bathochromic shifts of the major absorption bands. This alone suggested the presence of the Met-Tyr-Trp cross-link, as shifts for comparable aromatic-ring substitutions are predicted from theory (58) and observed in similar small molecule analogs, most notably for the cross-linked histidine-phenol mimic of cytochrome c oxidase (71), which exhibits a red-shift of ϳ20 nm of the phenol B (tyrosine) band (from 280 to ϳ300 nm).…”
Section: Fig 10supporting
confidence: 70%
“…Tyr I-288 is at the end of the K channel, hydrogen-bonded to the water on heme a 3 ( Figure 2). Oxygen reduction chemistry is likely to involve a coupled electron (92)(93)(94) and proton (75,95,96) transfer from this Tyr to O 2 . The Tyr could also serve as a proton acceptor when the BNC is reduced, if it is deprotonated in the fully oxidized state.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies of histidine-tyrosine model compounds have been reported (25)(26)(27)(28)(29)(30)(31)(32) supporting stabilization of a neutral tyrosine radical. However, the ligated copper, not included in these models, also is likely to affect the properties of the histidine-tyrosine dimer, which is the actual ligand of Cu B (33), and might increase its acidity and stabilize the neutral radical beyond that shown for the model compounds.…”
Section: Discussionmentioning
confidence: 98%